2013
DOI: 10.1590/s1413-35552012005000130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early treatment with transcutaneous electrical diaphragmatic stimulation (TEDS) on pulmonary inflammation induced by bleomycin

Abstract: BackgroundBleomycin (B) is an antineoplastic drug that has pulmonary fibrosis as a side effect. There are few experimental studies about the effects of physical therapy treatment in this case.ObjectiveThe objective was to study rat lungs treated with B and precocious intervention by transcutaneous electrical diaphragmatic stimulation (TEDS).MethodWistar rats were divided into 4 groups (n=5): a control group (C); a stimulated group (TEDS); a group treated with a single dose of B (intratracheally, 2.5 mg/kg) (B)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…We have previously demonstrated that MV induced TGF-β1 production as well as type I and III procollagen, lumican, and α-SMA gene expression in the diaphragm [30]. Other studies have reported increased oxidative stress and impaired energetic metabolism in the diaphragm in bleomycin-induced pulmonary inflammation [31] and lower glycogen content in the diaphragm in bleomycin-induced lung fibrosis [33]. However, our study is the first to investigate the mechanism underlying diaphragm fibrogenesis; we observed that bleomycin augments MV-induced diaphragmatic injury and contributes to diaphragm fibrosis in an animal model simulating critically ill patients receiving MV following ALI.…”
Section: Discussionmentioning
confidence: 85%
“…We have previously demonstrated that MV induced TGF-β1 production as well as type I and III procollagen, lumican, and α-SMA gene expression in the diaphragm [30]. Other studies have reported increased oxidative stress and impaired energetic metabolism in the diaphragm in bleomycin-induced pulmonary inflammation [31] and lower glycogen content in the diaphragm in bleomycin-induced lung fibrosis [33]. However, our study is the first to investigate the mechanism underlying diaphragm fibrogenesis; we observed that bleomycin augments MV-induced diaphragmatic injury and contributes to diaphragm fibrosis in an animal model simulating critically ill patients receiving MV following ALI.…”
Section: Discussionmentioning
confidence: 85%
“…We have previously demonstrated that MV induced TGF-β1 generation as well as type I and III procollagen, lumican, and α-SMA gene expression in the diaphragm [ 32 ]. Other studies have reported increased oxidative stress and impaired energetic metabolism in the diaphragm in bleomycin-induced pulmonary inflammation [ 33 ] and lower glycogen content in the diaphragm in bleomycin-induced lung fibrosis [ 34 ]. However, our study is the first to investigate the mechanism underlying diaphragm fibrogenesis; we observed that bleomycin augments MV-induced diaphragmatic injury and contributes to diaphragm fibrosis in an animal model simulating critically ill patients receiving MV following ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda de acordo com Cancelliero et al 8 a EDET tende a produzir uma contração por meio de uma corrente elétrica, com resposta sincrônica em todas as unidades motoras do músculo, provocando o recrutamento de fibras musculares diafragmáticas antes inativas. Devido a isso, este recurso fisioterapêutico é uma especificidade utilizada para melhorar a função ventilatória, auxiliando pacientes com fraqueza dos músculos respiratórios ou submetidos à VM 14 .…”
Section: Discussionunclassified